Arceoaster hintei n. gen. n. sp., a late Silurian homeomorphic asteroid (Echinodermata, Hudsonasteridae). (January 2021) - Blake, Daniel B.; Sprinkle, James
Abstract: The late Silurian Arceoaster hintei new genus new species (Asteroidea, Echinodermata) is based on a single complete specimen from the lower Hunton Group of southern Oklahoma. Overall ossicular arrangement enables assignment of the new genus to the Paleozoic stem-family Hudsonasteridae; however, Arceoaster n. gen. is homeomorphic with members of the post-Paleozoic crown-group Goniasteridae. Because Arceoaster n. gen. is a hudsonasterid, and because similar morphologic expressions are not known among described taxa from later in the Paleozoic or the early Mesozoic, similarities between Arceoaster n. gen. and later genera are homoplastic, thereby providing an example of iterative evolution within Asteroidea. The Arceoaster n. gen. specimen is associated with a rich and diverse invertebrate fauna typical of its time interval and environmental setting; nothing suggests an unusual habitat. Selective pressures leading to homoplasy are conjectural, although robust construction among extant asteroids has been associated with a defensive life strategy. UUID: http://zoobank.org/b1d8461d-7e54-43cc-8719-97304ca3fd7a